PENGUATAN KAPASITAS APARAT DESA DALAM IMPLEMENTASI PERATURAN DESA UNTUK PROGRAM PEMBANGUNAN BERKELANJUTAN - Hiola, Abdul samad; Junus, Dikson; Nuna, Muten; Napir, Suaib (Universitas Gorontalo, 2026)
The misalignment between Village Regulations (Peraturan Desa—Perdes) and village development planning documents remains a critical challenge in village governance in Indonesia. Inconsistencies among Perdes, the Village Medium-Term Development Plan (RPJMDes), the Village Government Work Plan (RKPDes), and the Village Budget (APBDes) often result in unfocused programs and increased legal vulnerability. This community engagement initiative aimed to strengthen the capacity of village officials in implementing Perdes to ensure that development programs are legally grounded and institutionally legitimate. The program was conducted in Bondula and Bihe Villages, Gorontalo Regency, on September 9, 2025, involving 30 village officials. A Participatory Action Research (PAR) approach was employed through an intensive eight-hour training session. Data were collected using pre-test and post-test assessments, participatory observation, and Focus Group Discussions (FGDs). The findings indicate a significant improvement in participants’ knowledge, with average scores increasing from 4.2 to 7.8 (an 85.7% increase; p < 0.001). Performance indicators exceeded expectations: 100% of participants were able to identify regulatory mandates within Perdes, and 86.7% successfully drafted program proposals aligned with Perdes provisions. Key outputs included four Perdes-based village program drafts with a total budget allocation of IDR 750 million, a synchronization matrix integrating Perdes with RPJMDes–RKPDes–APBDes, and an implementation roadmap. The collaboration between academia and international development programs proved effective in enhancing village governance capacity and demonstrates strong potential for replication to support sustainable rural development in Indonesia. . Keywords: Village apparatus capacity, sustainable development, village governance.